Genetic diversity analysis in sunflower (Helianthus annuus L.) germplasms: Genetic diversity analysis in sunflower (Helianthus annuus L.) germplasms - SAMPATH L; R SASIKALA; T KALAIMAGAL; V SANTHIYA; B J ANTONY (Journal of Oilseeds Research, 2023)
Evaluating genetic diversity in germplasm resources is a prerequisite for any effective breeding program. To classify sixty-six sunflower germplasm and seven checks, the study was conducted during 2020. The analysis of variance revealed significant differences among the genotypes for all characters. Divergence analysis using hierarchical cluster analysis (HCA) has been performed to effectively determining genetically distant parents, which could be used for hybridization. The HCA based on first three PCs grouped the lines into 8 clusters, where cluster IV had maximum number of genotypes. Additionally, it signifies that cluster I and cluster VIII are highly diverse, whereas cluster V and VI are less diverse.